The wine in traditional Roman medicine: between the sacred and the empirical - Cavicchioli, Marina Regis (Romanitas - Revista de Estudos Grecolatinos, 2025)
This study explores the crucial role that wine played in traditional Roman medicine. Wine was not only a foodstuff but also a therapeutic component used in healing practices and disease prevention. Its use has been evidenced since archaic times, in what could be termed primitive medicine and later evolved into traditional medicine based on ingredients sourced from forests and fields, often associated with libations and magical-religious rituals. Thus, this study explores the intersection between wine, magic, religion, and healing practices in ancient Rome, where the figure of the goddess Meditrina symbolizes this connection, representing healing, longevity, and wine itself. The work of Cato also provides insights into traditional Roman medicine while reflecting resistance to Greek influence and an appeal to preserve traditional Roman values. Therefore, wine is highlighted as a sacred and fundamental therapeutic substance in disease prevention and treatment, establishing a link between the practice of medicine and agriculture.
Keywords: Wine; Roman medicine; Healing practices; Magical-religious rituals; Meditrina; Cato